PENGARUH WORD OF MOUTH DAN PERCEIVED VALUE TERHADAP REPURCHASE INTENTION DILIHAT DARI PERBEDAAN JENIS KELAMIN PASIEN PADA RUMAH SAKIT PERTAMINA - Chrisnaldi Arif Zainal (Jurnal Manajemen dan Pemasaran Jasa, 2012)
Repeat business is important for service providers to be able to succeed in the current economic situation. Considering about the success of sales in General as seen from the number of repeat customers coming and still much cheaper cost to bring long term customers rather than looking for new customers, as well as developing efforts to redirect the customer to use the services ofhis return is critical for the continuity of the subject of a survival of a company. The goal of this research is to examine the behavior of post-consumer shopping includes word of mouth, perceived value, and repurchase intention in the sphere of business services. In addition, there is a gender role as moderator variables. Framework of the theory adopted from previous research to test each connection variables. An analysis of data before it has been revealed thatthere are gender influence of the relationship between word of mouth and perceived value of repurchase intention in the case study of a beauty salon. However, differences in the object of research, the number of samples, and the possible have different results. The findings in this study indicate that gender roles are not very significant in moderating relations word of mouth as well as the perceived value of repurchase intention. However, the perceived value and word of mouth have a significant influence in the repurchase intention. The result of this research has implications for the level of managerial hospital, in order to prevent negative news circulating among patients, second, to academics who want to develop a theory that advanced. Recommendations for further research are expected to be able to use the patients in otherHospitals as a comparison object of research, the addition of other variables also affect repurchase intention.Keywords; marketing, hospitality service, medical industry, Indonesia.